Caminhos trilhados pela educação física no Instituto Federal de Educação, Ciência e Tecnologia de Mato Grosso – Campus Cuiabá - Octayde Jorge da Silva - Almeida, Rogério Marques de (2011)
In this study we look for identifing and understanding the ways followed by Physical Education at the Federal Institute of Education, Science and Technology of Mato Grosso - IFMT Campus Cuiabá - Octayde Jorge da Silva since the year 1909 until 2002. For this, it has been theoretical-methodological subsidy the Cultural History, with a qualitative approach, whose primary sources were consulted official documents found in the permanent file and photographic registers, plus the narratives of teachers and former graduates of IFMT. From the analysis of data collected, it was possible to identify the ways followed by discipline, highlighting that between 1910 to 1934, for lack of documents and reports, in spite of formally present in the curriculum structure and legislation of the time, it couldn‟t be identified the existence of the practice of Physical Education. Between 1935 and 1944, we could claim that the school didn‟t offer physical education practices and not pre-military exercises, as recommended by the legislation of the period. From 1945, there isn‟t doubt about the presence of these practices, most notably the duration of the French method, through the united order, present to the end of the 1960s and calisthenics gymnastics, which endured until mid-1980. Considering that the sport emerges as a practice in the 1950s, as an option for the most skilful and still exists today, and that, this practice was extended to the less skilled and, in the 1980s, the students now have new possibilities of practices, such as dance, strength training, aerobics gymnstic and judo. The classes with obligatory nature were organized in anather turn and over the years, the weekly sessions were decreasing. The planning of lessons has never had a direction of integration to the institution's educational project, which the main objective of the classes, pointed out by teachers, was that students understand the importance of physical activity for life. The review process used by teachers was based on tests of physical fitness and frequency in the classroom. The infrastructure intended to Physical Education begins to receive attention in the 1950s, and it has received considerable financial support, it is possible to conclude that physical education has acquired a growing reputation in this educational institution. Could not be identified who were the teachers of Physical Education between 1910 and 1944. Between 1945 and 1972 we find professionals‟ registers of Instructor of Physical Education, arising out of the military and sport performance. In turn, the first graduate teachers in higher education and female arrived from other States in the 1970s, the decade of 1980 to begin graduate teachers hired by the newly created Faculty of Physical Education, Federal University of Mato Grosso. Of the former graduates surveyed only one of them said that physical education wasn‟t important in their education, others say that the classes were enjoyable despite repetitive and were important in their formation.